Macroeconomic effects of secondary market trading - Daniel Neuhann (European Central Bank (ECB), 2017)
This paper develops a theory of the credit cycle to account for recent evidence that capital is increasingly allocated to inefficiently risky projects over the course of the boom. The model features lenders who sell risk exposure to non-lender investors in order to relax borrowing constraints, but are tempted to produce and sell off bad assets when asset prices are sufficiently high. Asset prices gradually increase during the boom because non-lender wealth grows as their risk-taking pays off, triggering a fall in asset quality and precipitating an eventual crisis. I study the initial conditions that give rise to the credit cycle and consider policy implications.
Keywords: G01; E32; E44; 330; secondary markets; securitization; credit cycles; financial crisis; financial fragility; credit booms; saving gluts; risk-taking channel of monetary policy